Synthesis and application of nano-structured metal nitrides and carbides: A review. (June 2018) - Rasaki, Sefiu Abolaji; Zhang, Bingxue; Anbalgam, Kousika; Thomas, Tiju; Yang, Minghui
Abstract: Transition metal nitride and carbide have several similarities in their preparatory methods, properties, and applications. Synthetic parameters have remained the main factors that determine the effectiveness of nitrides and carbides in electrochemical storage devices, photocatalysis, environmental remediation, gas sensing and medicinal agents. This review addresses aspects of relevance to electronic structure and chemical bonding, and recent advances made in the synthesis approaches. The syntheses approaches that are particularly relevant for reducing (i) production cost, (ii) energy consumption, and (iii) synthesis time for these materials systems are discussed in detail. Furthermore some of the recent techniques like solid-solid state separation, carbothermal, gas-phase, electrochemical, sonochemical, solvothermal, sol-gel reaction and solid state reaction that offer new avenues for researchers (including a sustainability-oriented exploration) are mentioned. We discuss synthetically tunable properties (morphology, electronic characteristics, energy storage capacity, corrosion resistance, catalytic ability and gas sensing properties), heat treatment aspects, and relevant applications of these systems. We expect this review to be useful to the ever growing community of researchers that are interested in nitrides and carbides, and their applications.